Systems biology in biotech & pharma a changing paradigm - Prokop, Aleš (SpringerBriefs in pharmaceutical science & drug development, 2012)
Systems Biology (SB) is a suite of technologies and methodologies that resulted, conceptually from the merging of two basic paradigms, reductionism and holism. It represents a combination of reductionist and holistic approaches to the relationships among the elements of a system, with the goal of identifying its emergent properties and defining, quantitatively, molecular, cellular, tissue, organ and whole body processes. One manifestation of SB is as a tool for hypothesis generation about a system that is typically too large and complex to understand by simple reasoning. Abstract -- 1 Introduction: Discovery & Development - New Facet Of Industry, New Tools And Lead Optimization: 1.1 Scope And Content Of This Review -- 2 Discovery: Use Of Systems Biology For Identifying Targets -- 3 Integrative Systems Biology I - Biochemistry:  Phase I Lead Discovery & Molecular Interactions -- 4 Integrative Systems Biology Ii - Molecular Biology:  Phase 2 Lead Discovery & In Silico Screening -- 5. Discovery: Computational Systems Biology (Csb) In Health & And Disease I -- 6 Development:  In Vivo Pharmacology - Systems Biology In Health & Disease Ii -- 7 Development: Pharmacokinetics – Systems Biology In Health & Disease Iii -- 8 Development:  Multiscale Csb – Simulation Tools -- 9 Development:  Drug Formulation & Delivery -- 10 Development: Preclinical Model Based Drug Development -- 11 Systems Biology: Impact On Pharma And Biotech -- 12 Acknowledgment -- 13 Bibliography.